Piecing together the data of the U.S. marine aquaculture puzzle. (15th April 2022) - Froehlich, Halley E.; Gentry, Rebecca R.; Lester, Sarah E.; Rennick, Mae; Lemoine, Hayley R.; Tapia-Lewin, Sebastian; Gardner, Luke
Abstract: Aquaculture recently became the main source of global seafood production and many countries, including the United States, see potential in marine aquaculture to sustainably fill growing demand. The U.S. supports the majority of its seafood consumption through imports, and therefore identifying bottlenecks to domestic aquaculture growth is a priority at the federal and state level. Yet, one critical aspect that appears not yet addressed is the quality and accessibility of marine aquaculture data. In this study we conducted the first multi-state synthesis and comparison of the most comprehensive suite of species, volume, and value information on U.S. marine aquaculture over time, across the 23 marine coastal states. Using publicly available data sources from the U.S. Department of Agriculture (USDA), state-level solicited data that we aggregated, and data from the National Oceanic and Atmospheric Administration (NOAA), we found strong evidence that marine aquaculture has played an increasingly important role in marine coastal states, but also uncovered numerous data gaps and discrepancies between and within these sources. In particular, we found a dearth of volumetric data and millions in missing value (USD$). We found U.S. marine aquaculture is likely much more diverse, abundant and valuable than is currently reported, but the main sources of error in any given state remain unclear. We recommend U.S. state governments adopt a standardized, digital and annual data collection program, such as the NOAA Fisheries Information Networks. Better strategic aquaculture planning, management, and research depend on accurate data, and existing digital data infrastructures provide strong opportunities for improvement. Highlights: Accurate data is central to sustainable aquaculture planning and management, but is often overlooked. US marine aquaculture data sources have multiple gaps and discrepancies. The sector is likely more diverse, abundant, and valuable than is currently reported. At least 15 sources of error explain the data issues, many of them tied to the patchwork nature of US aquaculture policy. Adoption of a central, digital data platform could help address some data issues.